PERUBAHAN KADAR PROTEIN DAN STATUS LIPOSTATIK IKAN SIDAT, Anguilla bicolor, STADIA SILVER YANG DIPELIHARA PADA SALINITAS YANG BERBEDA - Sintia Novia Lestari; Farida Nur Rachmawati; Untung Susilo (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Eel (Anguilla bicolor) is a catradomous fish, in the growth phase of life in freshwater and upon reaching adult will migrate to ocean waters to reproduce. Eel during the migration will use energy from body reserves to osmoregulation. Increased salinity will affect the osmotic pressure of the body of the fish so that the fish do active transport which requires energy. Energy that used for osmoregulation approximately 20–50% of the total energy from carbohydrates, fats and proteins. Carbohydrates are the first source of energy that is used and then will be replaced by fat and protein as energy after carbohydrate depleted. Thus the energy utilization during osmoregulation will affect the changes in the composition of protein and fat content of the body. Fat content will affect the value of lipostatic fish is one of the growth parameters. The purpose of this study was to evaluate changes in the levels of protein and lipostatic eel (Anguilla bicolor) is maintained in a range of salinity. This research method is experimental research design with CRD, treatment in the form of maintenance medium salinity; 4 ppt (control), 15 ppt, and 30 ppt. Each treatment was repeated 5 times. Test fish used were obtained from the Village Pesanggrahan Cilacap with range size between an average weight of 395–920 g and an average length of 59–81 cm. The variables measured were the levels of protein and lipostatic eel. Protein content measurement was conducted using kjeldahl and the fat content by soxhlet. Research results showed that the eels were exposed to salinity 4 ppt, 15 ppt and 30 ppt no effect on protein content and body lipostatic eel. It can be concluded that the eel is able to adapt well in the range between 4 ppt salinity to 30 ppt.